An industrial example of using Enterprise Architecture to speed up systems development. Issue 1 (July 2017) - Sjöberg, Peter; Kihlström, Lars‐Olof; Hause, Matthew
Abstract: The development of large, complex, heavy construction equipment can be difficult, time consuming and expensive, even more so if the goal is to design a complete site solution. The example used is taken from an ongoing real project named Electric site. The aim is to electrify a transport stage in a quarry – from excavation to primary crushing and transport to secondary crushing. This will reduce the CO2 95% and the total cost of operation 25%. This paper describes how a standards‐based enterprise architecture model can be used to significantly influence continued system engineering efforts as well as the software architecture for the application development. The enterprise architecture model has been developed specifically to ensure overall management of the site. It is this description, created with an enterprise perspective of the site that is used directly to speed up the development of the systems architecture. The model also details the applications that are required as part of the different systems that will support the overall management of the site.